1966
DOI: 10.1002/ajpa.1330240306
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hereditary blood groups among Indians in South America. II. In Peru

Abstract: Blood specimens were procured from the following putatively pure Indians of the Peruvian rain forest: 90 Piro and 89 Campa on the Urubamba and Tambo rivers, 142 Shipibo and 14 Isconahua on the Rio Ucayali near Yarinacocha, 151 Aguaruna at Santa Maria de Nieva, where the Marañon and Nieva rivers join, and from 122 Ticuna and 9 Yagua near the Brazilian border on the Amazon. Specimens from highland Indians were obtained from 93 Aymará and 181 Quechua at Puno and environs. These 891 specimens were tested for antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
4

Year Published

1966
1966
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 58 publications
1
15
1
4
Order By: Relevance
“…As an example of this tendency, it can be seen that Guariba, the most easternly community, shows the lowest gene frequency, considering the six populations, in eight instances :(alleles L Ms pl, R e, R z, Fya, Di ~, Gc 1 and GALTD); while Cont~to (the most westernly) shows such lowest frequencies only once (Gmag). As for the Macushi weighted averages, they show good agreement with the previous blood group and haptoglobin investigations of Layrisse et al (1963), Arends and Gallango (1965) and Matson et al (1968). Exceptions are the L Ms p1, R 1, L e a and J k a frequencies, in which differences higher than 10% were found.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As an example of this tendency, it can be seen that Guariba, the most easternly community, shows the lowest gene frequency, considering the six populations, in eight instances :(alleles L Ms pl, R e, R z, Fya, Di ~, Gc 1 and GALTD); while Cont~to (the most westernly) shows such lowest frequencies only once (Gmag). As for the Macushi weighted averages, they show good agreement with the previous blood group and haptoglobin investigations of Layrisse et al (1963), Arends and Gallango (1965) and Matson et al (1968). Exceptions are the L Ms p1, R 1, L e a and J k a frequencies, in which differences higher than 10% were found.…”
Section: Resultssupporting
confidence: 89%
“…First hostile a m o n g themselves, they n o w live on good terms, sometimes forming mixed villages. The first genetic studies a m o n g them were performed by Layrisse, Layrisse and Wilbert (1963), Arends and Gallango (1965), Layrisse and Wilbert (1966) and Matson, Sutton, Pessoa, Swanson a n d Robinson (1968). Subsequently, Neel, Tanis, Migliazza, Spielman, Salzano, Oliver, Morrow and Bachofer (1977 a), Neel, Gershowitz, Spielman, Migliazza, Salzano a n d Oliver (1977b) and Salzano, Callegari-Jacques and Neel (1980) carried out more extensive studies which, inter alia, revealed a 'private' genetic polymorphism of E S A in rather high frequency in the Macushi and an adjacent tribe, the Wapishana, with no clear evidence of the tribe of origin.…”
Section: Introductionmentioning
confidence: 99%
“…Edwards' distances: MNSs,P,Rh,Duffy,Kidd,Diego,PGM1,ACP,GPT,ESD,GLO,Hp,Cp,Km,Gm, Our results can be considered in a wider context, using data from other Tupi tribes from which a reasonable amount of genetic information exists. We have been able to locate four such groups (Emerillon, Saterd-Maw~, Sirion6 and Waigpi;primary data presented in Fernet, Larrouy and Ruffi6 1964, Larrouy, Marti and Ruffi6 1964, Cabannes, Beurrier and Monnet 1965, Cabannes, Beurrier and Larrouy 1965, Matson, Swanson and Robinson 1966, Daveau, Rivat, Langaney, Afifi, Bois and Ropartz 1975, Quilici 1975, Vergnes, Quilici, Gherardi and Bejarano 1976, Tchen, Bois, S6ger, Grenand, Feingold and Feingold 1978, Tchen, Bois, Lanset and Feingold 1981, Black, Salzano, Berman, Gabbay, Weimer, Franco and Pandey 1983, Hamel, Salzano and Freitas 1984, Salzano, Weimer, Franco, Hutz, Mestriner, Sim6es and Freitas 1985. The resulting matrices and dendrograms are shown in table 5 and figure 3.…”
Section: Resultsmentioning
confidence: 89%
“…The gene frequency data of blood groups and proteins were collected from the Athabaskan Indians in Alaska [I, 3,24,25], five linguistic groups in Mexico [4,5,8,[12][13][14][15][16], the Makiritare in Venezuela [2,9,26], the Yanomama in Brazil [10,27,28] and the Campa and the Quechua tribes in Peru [17,18].…”
Section: Methodsmentioning
confidence: 99%